Exploring the role of Human Resource Management (HRM) practices, organizational commitment, and organizational performance in Malaysian State Sports Council / Nur Syazwani Zulaikha Safwan - Safwan, Nur Syazwani Zulaikha (2024)
Organizational performance can be evaluated through the effectiveness of Human Resource Management (HRM) practices implemented in the organization. However, the problem of improper and misguided implementation of HRM practices causes conflict between employees and organizations, influencing commitment and performance. This study examines the role of HRM practices, organizational commitment, and organizational performance among Malaysian State Sports Councils’ (MSSC) employees by adapting the Social Exchange Theory and Organizational Commitment Model. This survey involved a total of 280 MSSC employees. The research instrument included 48 items designed to assess HRM practices, organizational commitment, and organizational performance. Data analysis was carried out using descriptive, inferential, and Structural Equation Model (SEM) using Analysis of Moment Structures (AMOS) software. Based on the findings, four dimensions of HRM (recruitment and selection, reward, performance appraisal, and participation and communication) were high, while training and development were moderate. The organizational commitment (affective and continuance) was at a moderate level, and normative commitment was at a high level. In the meantime, organizational performance was reported at a high level. Besides, the result also indicates a significant and direct effect between variables and organizational commitment partially mediates between HRM practices and organizational performance. In conclusion, the organization’s excellent structure of HRM practices enables employees to commit to work and perform tasks according to the organizational goals. Future researchers should extend the study sample to other sports organizations or other public and private organizations in measuring HRM practices, organizational commitment, and organizational performance.